А method of surgical correction of genital prolapse in combination with elongation and cicatricial deformation of the cervix in patients of reproductive age. A retrospective study - Albina Kh. Karanasheva; Yulia E. Dobrokhotova (Гинекология)
Aim. To improve reproductive health and quality of life of patients with genital prolapse combined with elongation, cicatricial deformation of the cervix.